Pengaruh Pencahayaan Buatan Terhadap Gejala Kelelahan Mata Subyektif di Pondok Pesantren Al-Qodir Dusun Tanjung Desa Wukirsari Kecamatan Cangkringan Kabupaten Sleman - Andi Setiawan; Yamtana Yamtana; Sri Puji Ganefati (Poltekkes Kemenkes Yogyakarta, 2009)
One objectives of health development is to improve the ability of healthy life for everyone in order to reach their optimal health degree. There are some physical factors that influence public health, e.g. inadequate illumination. Inappropriate illumination can disturb the health of eyes. The goal of the study was to understand the appropriate level of artificial illumination used for reading activities in Al-Qodir Moslem Boarding School at Tanjung Village, Wukirsari, Cangkringan, Sleman. The study was an experiment with ’post-test only design’. The study subjects were high school level students. Meanwhile, the treatments were 100, 200 and 300 lux artificial illumination. The subjective eyes fatigue symptoms were observed by using questionnaire and then classified as: high, medium, and low. For each illumination treatment, the procentage of the symptom classifications are as follows: 100 lux: high 53,3%, medium 33,3%, low 13,4%; 200 lux: high 13,5%, medium 20,0%, low 66,5%; and 300 lux: high 40,0%, medium 40,0%, low 20,0%. Based on the results, it was concluded that the appropriate illumination intensity for the boarding school was 200 lux, because this treatment was the highest procentage in the low ’category’. Furthermore, it was advised for school managerial board to provide the requisiteillumination by installing 40 watt flourescent lamps or providing 14 watt table lamps; and to avoid excessive glare, the installation should carefully considering the appropriate distance between the lamps and reading areas.